Res Publica A Journal of Moral, Legal and Political Philosophy - Laegaard, Sune.; Cook, Philip; Chambers, Clare; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Res Publica: a Journal of Legal, Moral and Social Philosophy is an interdisciplinary publication concerned with the philosophical analysis of moral, political, social and legal issues. It provides a forum for discussion of theoretical issues; a public arena for voicing matters of practical concern; and a vehicle for addressing questions of morality, politics, law and society, the interconnections between them and, more generally, the relation of theory to practice. The journal seeks to publish articles and review essays which are both philosophically rigorous and accessible to a wide range of academics and professionals. Replies to articles are welcome. It is the policy of Res Publica to encourage publication by researchers at the beginning of their careers as well as by established scholars; and by those in non-Western countries.
Keywords: Political theory; Ethics; Political philosophy; Law -- Philosophy; Law; Political Philosophy; Theories of Law, Philosophy of Law, Legal History; Political Theory; Theories of Law, Philosophy of Law, Legal History; Ethics